Anxiety and depression in patients with cervical cancer before surgical treatment - Stanimirović Ljiljana (Association of Nurses Technicians and Midwives, 2017)
As part of the Liaison Psychiatry, psycho-oncology takes important place with the goal of adequate treatment of oncology patients. At the end of last century, the first phase of the development of this area is marked by dilemma, whether to tell the patient what is suffering of and how to do it. Cervical cancer is the most common diseases of women genital organs and in the last few years, trend shows the increase of illness and mortality. Overall low level of health culture in general population, as well as late recognition of symptoms, results in late cure treatment. In addition to the biological nature of causes - Human Papiloma virus, the illness is affected by emergence of psychical factors, which is described throughout the history of medicine. Women temper and character is the basis for emotional reaction of psychological factors. Studies had shown that women, who are emotionally inhibited with reduced capacity for emotional discharge, were predisposed for malignant diseases. Psychological response to somatic diseases and, in general, attitudes towards physical illness is different and individual. Research confirms the always present anxiety, already at the first examination by a gynecologist, indicates a fear of uncertainty. Confirmation of diagnosis of malignant diseases and expected treatment, in addition to anxiety, can lead to a diagnosis of depression, mood disorder and sexual dysfunction. In common psychological practice are in use various scales, test and questionnaires for assessment of anxiety, depression, stress level, quality of life, psychological defense mechanisms, all that convey trough through team work.